DO GREEN ACCOUNTING AND CARBON EMISSION DISCLOSURE AFFECT STOCK RETURN? - Diva Sarvasti, Laily; Astrini Aning Widoretno (Faculty of Economics and Business University of Mataram, 2024)
Environmental issues such as climate change can be an external factor that influences stock price fluctuations and stock returns. This research aims to analyze the impact of carbon emission disclosure, green accounting practices, and profitability on the share returns of food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2020 to 2022. This research uses a quantitative approach, multiple linear regression analysis methods, and a sample of 54 companies. The results of this study indicate that profitability has a significant impact on stock returns. However, carbon emission disclosure and green accounting do not significantly impact stock returns. The results of this research can be a reference for companies and investors who want to pay closer attention to environmental conditions.